Enajenación y malestar: tensiones conceptuales entre el marxismo y el psicoanálisis - Hernández Delgado, Rigoberto (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
In this work we examine the possible relationships between the concepts of alienation and discontent, coming from the theory of Marx and Freud respectively -but also developed by many other authors and schools-, in their various levels and aspects, in order to find some articulation that makes it possible to explain the problems related to the phenomena that these terms designate in the context of capitalist relations of production. It begins by tracing, synthesizing and analyzing the concept of alienation in some texts written by Marx, as well as other concepts related to it, for example: work, objectification, merchandise fetishism, etc. In a second moment we examine the development of the concept of discomfort in Freud's work, analyzing its relationships with other Freudian concepts such as: repression, drive, superego, etc. In a third moment, we addressed the Marxist and Freudian developments around discontent and alienation carried out by three thinkers of the Frankfurt School: Theodor Adorno, Max Horkheimer and Herbert Marcuse. The work is finished by means of an outline of organization and schematization of the relationships between the concepts addressed throughout the work, to try to define the conceptual relationships between our main categories: alienation and discontent.

En este trabajo se examinan las relaciones posibles entre los conceptos de enajenación y malestar, provenientes de la teoría de Marx y de Freud respectivamente -pero desarrollados también por muchos otros autores y escuelas-, en sus diversos niveles y aspectos, para poder encontrar alguna articulación posible que permita explicar los problemas relativos a los fenómenos que estos términos designan en el contexto de las relaciones de producción capitalistas. Se inicia rastreando, sintetizando y analizando el concepto de enajenación en algunos textos escritos por Marx, así como otros conceptos relacionados con éste, por ejemplo: trabajo, objetivación, fetichismo de la mercancía, etc. En un segundo momento se examinar el desarrollo del concepto de malestar en la obra de Freud, analizando sus relaciones con otros conceptos freudianos tales como: represión, pulsión, superyó, etc. En un tercer momento se abordan los desarrollos marxistas y freudianos en torno al malestar y la enajenación llevados a cabo por tres pensadores de la Escuela de Frankfurt: Theodor Adorno, Max Horkheimer y Herbert Marcuse. Se finaliza el trabajo mediante un esbozo de organización y esquematización de las relaciones entre los conceptos abordados a lo largo del trabajo, para tratar de definir las relaciones conceptuales entre nuestras categorías principales: enajenación y malestar.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2021-1443; Fetichismo; Trabajo; Represión; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6519